Social media engagement as a mediator of viral marketing, brand image, and Aerostreet purchase intention - Muhammad Ifanto Kurniawan; I Made Bagus Dwiarta (Manajemen dan Bisnis, 2026)
The development of social media, especially TikTok, has transformed digital marketing strategies by encouraging more intense interactions between brands and consumers. This research explores the relationships between viral marketing, brand image, and purchase intention, with social media engagement serving as a mediator among TikTok users of the Aerostreet shoe brand in Surabaya. This research applies a quantitative approach with data collection through surveys, involving 160 purposively selected respondents. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. Empirical findings show a significant relationship between social media engagement and purchase intention.. In addition, the findings reveal that social media engagement exerts a significant influence on purchase intention. The mediation analysis further confirms that social media engagement serves as a meaningful intervening mechanism through which viral marketing and brand image affect consumers’ purchase intention. These results highlight the critical role of interactive and emotionally engaging content in shaping purchasing decisions, particularly within the TikTok environment. The findings of this study not only contribute to strengthening digital marketing literature, but also provide practical benefits for MSMEs in increasing the effectiveness of marketing communications through social media.